Genome-Based Analysis of Extended-Spectrum β-Lactamase-Producing Escherichia coli in the Aquatic Environment and Nile Perch (Lates niloticus) of Lake Victoria, Tanzania - Baniga, Zebedayo; Hounmanou, Yaovi M. Gildas; Kudirkiene, Egle; Kusiluka, Lughano J. M.; Mdegela, Robinson H.; Dalsgaard, Anders (Frontiers in Microbiology, 2020)
Extended Spectrum Beta-Lactamase (ESBL) producing bacteria constitute an emerging global health issue with food products being vehicles of transmission and the aquatic environments serving as potential reservoirs. This study aimed to characterize ESBL-producing E. coli in Nile perch and water from Lake Victoria in Tanzania. A total of 180 samples of Nile perch and 60 water samples were screened for ESBL-producing E. coli on MacConkey agar supplemented with 2 µg/ml of cefotaxime and confirmed by blaCTX-M and blaTEM PCR. Antimicrobial resistance was determined by the disc diffusion method and ESBL-producing isolates were whole genome sequenced (WGS). ESBL-producing E. coli were detected in eight of the 180 analysed Nile perch samples and only one water sample was positive (1.7%, n=60). Isolates were resistant to sulphamethoxazole-trimethoprim (100%), ampicillin/cloxacillin (100%), erythromycin 72.7% (8/11), tetracycline 90.9% (10/11) and nalidixic acid 63.6% (7/11). This mostly corroborates the resistance genes that they carried for sulphonamides (sul1 and sul2), trimethoprim (dfrA and dfrB), aminoglycosides (aac(3)-IId, strA and strB), tetracycline (tet(B) and tet(D) and fluoroquinolones (qepA4). They harboured plasmid replicon types IncF, IncX, IncQ, Col and carried blaCTX-M-15 and blaTEM-1B genes generally found on the same contigs as the IncF plasmid replicon. Although epidemiologically unrelated, the strains formed three separate sequence type-phylogroup-serotype specific clusters: C1, C2 and C3. Cluster C1 included five strains (3 to 13 SNPs) belonging to ST167, phylogroup A, and serotype O9:H21; two C2 strains (11 SNPs) belong to ST156, phylogroup B1, and serotype ONT:H28, and C3 was made of four strains (SNPs ranged from 4 to 17) of ST636, phylogroup B2, and serotype O45:H7. The common virulence gene gad was reported in all strains. In addition, strains in C2 and C3 possessed iss, lpfA and nfaE virulence genes and vat gene was found in C3. The present study reports the occurrence of multidrug-resistant ESBL-producing E. coli carrying plasmid-mediated ESBL genes in off-shore water and Nile perch in Lake Victoria. Strains formed three clonal clusters of unknown origin. This study reveals that the Lake may serve as reservoir for ESBL-producing bacteria that can be transmitted by fish as a food chain hazard of One-Health concern.